The heterogeneity of Campylobacter jejuni and Campylobacter coli strains isolated from healthy cattle - Açik, MN; Çetinkaya, B (Oxford Univ Press, 2005)
Aims: To identify campylobacters isolated from clinically healthy cattle at species level by a multiplex polymerase chain reaction (m-PCR). The heterogeneity among Campylobacter jejuni and Campylobacter coli isolates was also investigated by using a restriction fragment length polymorphism (RFLP) analysis of flagellin (flaA) gene. Methods and Results: Samples of intestinal contents, gall bladders, liver and faeces were collected from a total number of 1154 healthy cattle. The samples were inoculated onto Preston enrichment broth and agar. Of 1154 samples, 301 (26.1%) were positive for Campylobacter spp. Using an m-PCR assay for species identification, 179 (59.5%) were positive with C. jejuni specific primers while 30 (10%) were positive with C. coli specific primers. None of the liver samples examined was positive for C. jejuni or C. coli by mPCR. All the isolates identified as C. jejuni and C. coli were successfully subtyped by flaA typing. Of the 209 isolates tested, 28 different flaA types were found. Twenty-three flaA types were identified among 179 C. jejuni isolates and the remaining five from C. coli isolates. Conclusions: Although the overall results suggest that the degree of heterogeneity among the flaA genes of thermophilic Campylobacter strains isolated from healthy cattle is relatively high, they should be treated cautiously as the number of band types for C. coli was low and band type 8 in C. jejuni was represented by a high percentage (%58). Siognificance and Impact of the Study: The findings of the present study suggest that healthy cattle can play role in the contamination of environment and human food chain by Campylobacter spp.
Keywords: Campylobacter jejuni; Campylobacter coli; flaA gene; healthy cattle; multiplex polymerase chain reaction; restriction fragment length polymorphism